2006
DOI: 10.1073/pnas.0511048103
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical measurements of the sequence-dependent folding landscapes of single nucleic acid hairpins

Abstract: Nucleic acid hairpins provide a powerful model system for probing the formation of secondary structure. We report a systematic study of the kinetics and thermodynamics of the folding transition for individual DNA hairpins of varying stem length, loop length, and stem GC content. Folding was induced mechanically in a highresolution optical trap using a unique force clamp arrangement with fast response times. We measured 20 different hairpin sequences with quasi-random stem sequences that were 6 -30 bp long, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
566
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(636 citation statements)
references
References 58 publications
67
566
2
1
Order By: Relevance
“…4.4A shows the first type of unfolding behavior, termed "Type 1" in which the A24G mutant unfolds in a single step at some force, F, but upon relaxation (red curve) refolds event at a lower force than the unfolding force. This behavior had not been observed for the wild-type BWYV pseudoknot or the mutants stretched up to this point (see Chapter 3), but the behavior has been observed for RNA hairpins and pseudoknot structures (26,28,51,106). It signifies that the refolding kinetics is slower than the pulling rate, but that we may be approaching an equilibrium state were the stretching performed slightly slower (perhaps 1-2 pN/s slower).…”
Section: Stretching Of An A24g Mutant Pseudoknotmentioning
confidence: 87%
“…4.4A shows the first type of unfolding behavior, termed "Type 1" in which the A24G mutant unfolds in a single step at some force, F, but upon relaxation (red curve) refolds event at a lower force than the unfolding force. This behavior had not been observed for the wild-type BWYV pseudoknot or the mutants stretched up to this point (see Chapter 3), but the behavior has been observed for RNA hairpins and pseudoknot structures (26,28,51,106). It signifies that the refolding kinetics is slower than the pulling rate, but that we may be approaching an equilibrium state were the stretching performed slightly slower (perhaps 1-2 pN/s slower).…”
Section: Stretching Of An A24g Mutant Pseudoknotmentioning
confidence: 87%
“…This approach has answered one of the most fundamental questions in nucleic acid structure formation, providing direct evidence for the long-held nucleation model for duplex involving formation of 2-3 base pairs prior to rapid formation of the remainder of the duplex [107]. Further, it has been shown that force unfolding data can be deconstructed into a complete energy landscape [108].…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…Woodside et al recently measured the thermodynamics and kinetics of 20 different DNA hairpins with different stem lengths, G·C content and loop sizes (Woodside et al 2006). Their work illustrates how folding free energies and rate constants critically depend on the sequences and structures of the hairpins.…”
Section: Kinetics Of Unfolding-mentioning
confidence: 99%